The Effectiveness of Electronic Mediation in Religious Courts Based on Supreme Court Regulation No. 3 of 2022 concerning Electronic Mediation in Courts (Case Study at the Karawang Religious Court) - Lia Amaliya; Farhan Asyhadi; Aef Sulaeman; Imas Rosidawati (PT. Anagata Sembagi Education, 2025)
Advances in information technology have driven significant transformations in supply chain management, including in the healthcare logistics sector, which requires fast, precise, and safe distribution. One recent innovation is the integration of conventional transportation with autonomous vehicles (AVs) in the distribution of healthcare products. This study aims to analyze the effectiveness of this hybrid healthcare logistics model by assessing its impact on distribution speed, cost efficiency, and product safety. The research method used a mixed methods approach, involving a quantitative survey of 120 respondents consisting of hospital logistics managers, transportation providers, and regulators, as well as in-depth interviews with 10 industry experts. Quantitative data were analyzed using multiple linear regression tests to measure variable relationships, while qualitative data were analyzed using thematic analysis to gain insights into field implementation. The results showed that the integration of AVs with conventional transportation increased distribution speed by up to 27% and reduced operational costs by an average of 18%, while also improving product safety through sensor systems and real-time monitoring. However, regulatory and infrastructure constraints are factors that hinder widespread adoption. These findings confirm that hybrid healthcare logistics can be a strategic solution in modernizing healthcare product distribution, provided it is supported by adaptive policies and inclusive technology development.